The Effect of Company Sizes and Net Working Capital on Cash Holding With Profitability as Intervening Variables in Food and Beverage Sub Sector Companies Registered in Indonesia Stock Exchange - Murtiadi Awaluddin; Elis Elis; Sri Prilmayanti Awaluddin; Rulyanti Susi Wardhani; Syarif Syharir Malle (Universitas Islam Negeri Alauddin Makassar, 2020)
The COVID-19 pandemic that has hit the world including Indonesia since early 2020 has had The purpose of this study was to determine and analyze the influence of company size and net working capital towards holding cash with profitability as an intervening variable. This Research uses quantitative methods with 2013-2017 observation years. The research sample consisted of 15 food and beverage sub-sector companies listed on the Indonesia Stock Exchange, while the method used was purposive sampling. The analytical method used is multiple linear regression and path analysis. The results showed the size of the company had a negative and not significant effect on profitability, net working capital was positive and not significant on profitability. Company size, net working capital, and profitability have a positive and significant influence on cash holding. Profitability is not able to mediate the effect of company size on cash holding.But profitability is able to mediate the effect of net working capital on cash holding